1, 3, 4‐oxadiazole and its derivatives: A review on recent progress in anticancer activities. (27th September 2020) - Vaidya, Ankur; Pathak, Devender; Shah, Kamal
Abstract: The 1, 3, 4‐oxadiazole nucleus is a biologically imperative scaffold possesses numerous biological activities. The broad and potent activity of 1, 3, 4‐oxadiazole and their derivatives has established them as important pharmacological scaffolds especially in the treatment of cancer disease. Several di‐, tri‐, aromatic, and heterocyclic substituted 1, 3, 4‐oxadiazole derivatives have been reported to possess potent anticancer activity. These substituted 1, 3, 4‐oxadiazoles had shown different mechanism of action and participated in anticancer drug discovery and development. This review is complementary to earlier reviews and aims to review the work reported on anticancer activities of 1, 3, 4‐oxadiazole derivatives from year 2000 to the beginning of 2020. Abstract : This review is complementary to earlier reviews and aims to review the work reported on anticancer activities of 1, 3, 4‐oxadiazole derivatives from year 2000 to the beginning of 2020.